Comunicação e direito à saúde - Pilau Sobrinho, Liton Lanes (Universidade do Vale do Rio do Sinos, 2008)
The thesis held orients itself towards the analysis of the dichotomy likely / unlikely communicational health. Using Luhmann´s systems theory we are seeking to entangle in communicative analysis of the phenomenon of communication / non-communication as a way of effectiveness of the right to health. The health presents as a very complex reality, the concentration thus a paradox: there is a guarantee the maintenance and health care for all by the government, however the Brazilian reality reflects a reality different from that crystallized in the constitutional text, reflecting a complete failure state as far as their promotion. Thus, considering the conception of society as communicative system, the question proposed is given precisely towards checking the possibilities of communication, exemplified by AIDS and Alzheimer´s Disease to view the constant viability of the constitutional guarantee to health. There is, therefore, health divided by communicative aspects and non-communicative, which lie precisely impro
Keywords: direito à saúde; improbabilidade; meios de massa; opinião pública; comunicação; improbability; mass media; public opinion; right to health; communication; Ciências Sociais Aplicadas